(untitled) (Palíndromo, 2026)
The article analyzes the perceptive structures of the Sublime from a critical perspective, aiming to outline an aesthetic-geopolitical construction in dialogue with the notion of Landscape. Methodologically, a historical-conceptual survey was conducted to link 17th-century European imperialism in Brazil to modern liberalism and contemporary capitalism, utilizing the notion of commodity as a category of mediation. As a result of the colonial triangulation of these periods, the aesthetic and political effects of Pornobarbarism on bodies and territories are identified. It is concluded that the insurgency of the Sublime emerges as an aesthetics of the in-common, grounded in decolonial cosmovisions capable of recognizing Nature as a subject of rights, overcoming Western aesthetic utilitarianism through communion and co-belonging to the territory.